Karakteristik Proses Metakognisi Mahasiswa dalam Menyelesaikan Masalah Kalkulus - Dwi Purnomo (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
The study aims at analyzing and describing characteristics of the students’ meta cognition process in completing calculus about function limit application to determine maximum and minimum scores through awareness, evaluation, and regulation as the components. The study involves 23 students of mathematic education department having took differential calculus as the subject. The data of the research were work result, think aloud recording, observation sheet, questionnaire response, and interview manuscript. The group work result were categorized into highly, medium, and low capable subjects. The data collected were then analyzed using comparative method of Glaser and Strauss. Based on the data analysis, it was found that characteristics of the students’ meta cognition process were categorized into highly, medium, and low capable subjects with awareness, evaluation, and regulation indicators the process of which occurred completely, respectively, completely irrespectively, and irrespectively